Ad
  • Custom User Avatar

    This comment is hidden because it contains spoiler information about the solution

  • Default User Avatar
  • Default User Avatar
  • Default User Avatar

    'alr approved some time ago'

  • Custom User Avatar

    I still don't get where the (b - 1) * fib(n + 2) = (b - 1) * fib(n) + (b - 1) * fib(n + 1) comes from and why should I add this to the original equation. Please, explain in details or give me link to a book or some article where it is well-explained.

  • Custom User Avatar

    @Technetium_Phenol Oh, C'mon :D It's 21st century, forget Fortran and come to Scala :D

  • Default User Avatar

    The description is not correct.
    they have fib(0) = 1
    and there code doesn't calculate the fibonnaci series.

    Here is my alternative expansion.

    The function is recursively defined by:

    0.    fib(0) = 0
    1.    fib(1) = 1
    2.    fib(2) = 1
    3.    fib(n + 2) = fib(n) + fib(n + 1), if n + 2 > 1
    If one translates the above definition directly into a recursive function, the result is not very efficient. One can try memoization, but that requires lots of space and is not necessary. So, first step is to try and find a tail recursive definition. In order to do that we try to write both sides of equation 3) on the same form. Currently, the left side of the equation contains a single term, whereas the right side is the sum of two terms. A first attempt is to add fib(n + 1) to both sides of the equation:

    3.    fib(n + 1) + fib(n + 2) = fib(n) + 2 * fib(n + 1)

    The two sides of the equation look much more alike, but there is still an essential difference, which is the coefficient of the second term of each side. On the left side of the equation, it is 1 and, on the right, it is 2. To remedy this, we can introduce a variable b:

    3.     b * fib(n + 1) + b * fib(n + 2) = b * fib(n) + (b + b) * fib(n + 1)

    We then subtract both sides by b * fib(n+1)

    3.     b * fib(n + 2) = b * fib(n) + (b + b)

    To try and return the tail to the function we add both sides by a * fib(n+1) to each side:

    3.     a * fib(n + 1) + b * fib(n + 2) = b * fib(n) + (a + b) * fib(n + 1)

    Now the two sides have the same form (call it F), this function has the form:

    3.     F(c, d, e) = F(a, b, n+1) = F(a, a+b, n) = c * fib(e) + d * fib(e + 1)

    (Note if your confused by the above equation substitute the values into the furthest right function and you get)

    3.     a * fib(n + 1) + b * fib(n + 2) = b * fib(n) + (a + b) * fib(n + 1) = c * fib(n) + d * fib(n + 1)

    Which we can simplify to:

    3.     F(a, b, n + 1) = F(b, a + b, n)

    We also have, by definition of F and fib:

    4.     F(a, b, 0) = a * fib(0) + b * fib(1) = b

    (Proove this with general equation)
    F(a, b, n + 1) with n = 0
    c * fib(n) + d * fib(n + 1)
    a * fib(0) + b * fib(0 + 1) as fib(0) = 0, fib(1) = 1
    b
    Also, by definition of F:
    5\.     fib(n) = F(1, 0, n) with a = 1, b = 0
    (Proove this with general equation)
    c * fib(e) + d * fib(e + 1)
    1 * fib(n) + 0 * fib(n + 1)
    1 * fib(n)
    6\.     F(a, b, 1) = a * fib(1) + b * fib(2) = a + b
    (Proove this with general equation)
    F(a, b, n + 1) with n = 1
    c * fib(n) + d * fib(n + 1)
    a * fib(1) + b * fib(1 + 1) as fib(1) = fib(2) = 1
    a + b
    The next step is to translate the above into code:
    def fib(n):
        if n == 0: return 0    # see 6. above
        def F(a, b, n):
            if n == 1: return a + b    # see 6. above
            return F(b, a + b, n - 1)  # see 3. above (F(a, b, n + 1) = F(b, a + b, n)) use n = n - 1
        return F(1, 0, n)              # see 5. above
    

    The final step (optional for languages that support tail call optimization) is to replace the tail recursive function F with a loop:

    def fib(n):
        if n == 0: return 0            # see 4. above
        a, b = 1, 0                    # see 5. above
        while n > 1:		
            a, b, n = b, a + b, n - 1  # see 3. above
        # n = 1 at this point
        return a + b<>                   # see 6. above 
    
  • Custom User Avatar

    (1) that each golfer plays "exactly once every day"
    That means same set of players everyday.

  • Custom User Avatar

    GO Language Translation Added :D

  • Custom User Avatar

    I made the same mistake, I thought it meant they could play at least once and checked for playing and rejected if they did not play with every other player.

  • Custom User Avatar

    What does it mean by "Must reject an unknown player: True should equal False"

    Do the playeres have to be sequential from "A" to "Z" or is there characters other than alpha tested for and those should be rejected?

  • Default User Avatar

    This comment is hidden because it contains spoiler information about the solution

  • Custom User Avatar

    haha, no worries, just repond here or msg me if people complain.
    I am fairly decent at Fortran, so it shold work with out problems.

    Thanks for the approval.

  • Custom User Avatar

    Thanks, approved. I don't know a thing about Fortran, so hopefully it's ok... :)

  • Custom User Avatar

    I agree, some of the Kata's are really easy in some languages and rediculously hard in other langauages.
    It is a shame that kata ranks can be language dependent.

  • Loading more items...